Chinese Semiotic Studies (De Gruyter Mouton, 2009)
Chinese Semiotic Studies (CSS) is a peer-reviewed journal sponsored by the International Institute of Semiotic Studies of Nanjing Normal Universityand the Chinese Semiotic Research Center of the Chinese Association of Linguistic Semiotics. As the only semiotics journal in China appearing in English, CSS is a unique outlet for Chinese scholars to be heard in western academia, expanding the dialogue between Chinese and western semioticians.